Functional differentiation of Sec13 paralogues in the euglenozoan protists - Faktorová, Drahomíra; Záhonová, Kristína; Benz, Corinna; Dacks, Joel B; Field, Mark C; Lukeš, Julius (Open biology, 2023)
The β-propeller protein Sec13 plays roles in at least three distinct processes by virtue of being a component of the COPII endoplasmic reticulum export vesicle coat, the nuclear pore complex (NPC) and the Seh1-associated (SEA)/GATOR nutrient-sensing complex. This suggests that regulatory mechanisms coordinating these cellular activities may operate via Sec13. The NPC, COPII and SEA/GATOR are all ancient features of eukaryotic cells, and in the vast majority of eukaryotes, a single Sec13 gene is present. Here we report that the Euglenozoa, a lineage encompassing the diplonemid, kinetoplastid and euglenid protists, possess two Sec13 paralogues. Furthermore, based on protein interactions and localization studies we show that in diplonemids Sec13 functions are divided between the Sec13a and Sec13b paralogues. Specifically, Sec13a interacts with COPII and the NPC, while Sec13b interacts with Sec16 and components of the SEA/GATOR complex. We infer that euglenozoan Sec13a is responsible for NPC functions and canonical anterograde transport activities while Sec13b acts within nutrient and autophagy-related pathways, indicating a fundamentally distinct organization of coatomer complexes in euglenozoan flagellates.
Keywords: buněčná diferenciace; Eukaryotic Cells; membrane trafficking; Cell Differentiation; Eukaryota; paralogue expansion; nuclear pore complex; Diplonema; coatomer; jaderný pór; SEA/GATOR complex; eukaryotické buňky; Euglenozoa; Nuclear Pore